Training in metabolomics research. I. Designing the experiment, collecting and extracting samples and generating metabolomics data. (July 2016) - Barnes, S.; Benton, H. P.; Casazza, K.; Cooper, S. J.; Cui, X.; Du, X.; Engler, J. A.; Kabarowski, J. H.; Li, S.; Pathmasiri, W.; Prasain, J. K.; Renfrow, M. B.; et al.
Abstract : Metabolomics is perhaps the most challenging of the ‐omics fields, given the complexity of an organism's metabolome and the rapid rate at which it changes. When one sets out to study metabolism there are numerous dynamic variables that can influence metabolism that must be considered. Recognizing the experimental challenges confronting researchers who undertake metabolism studies, workshops like the one at University of Alabama at Birmingham have been established to offer instructional guidance. A summary of the UAB course training materials is being published as a two‐part Special Feature Tutorial. In this month's Part I the authors discuss details of good experimental design and sample collection and handling. In an upcoming Part II, the authors discuss in detail the various aspects of data analysis.